Efficacy, safety, and acceptability of thermocoagulation for treatment of cervical intraepithelial neoplasia in a hospital setting in Brazil. Issue 3 (2nd March 2016) - Naud, Paulo S.V.; Muwonge, Richard; Passos, Eduardo P.; Magno, Valentino; Matos, Jean; Sankaranarayanan, Rengaswamy
Abstract: Objective: To analyze the acceptability, safety, and effectiveness of thermocoagulation for the treatment of histologically proven cervical intraepithelial neoplasia grade 2–3 (CIN2–3) lesions. Methods: In a retrospective study, data were obtained for women treated for CIN2–3 lesions by thermocoagulation at the Hospital de Clínicas de Porto Alegre, Brazil, between March 6, 2012, and October 29, 2013, and followed up after 1 year. The proportions of women with no evidence of disease, adverse effects, or complications were determined. Results: Among 52 women included, 44 (85%) had no evidence of disease 1 year after thermocoagulation. The rate of no disease at follow‐up was similar for women treated for CIN2 (17/20 [85%]) and CIN3 (27/32 [84%]). No serious adverse effects or complications requiring hospitalization were observed during the follow‐up period. Conclusion: Thermocoagulation is useful in the management of ectocervical CIN and should be integrated into public health services for management of cervical cancer.